Molybdenum oxychloride with improved bulk density
By using molybdenum oxychloride consolidated masses with high molybdenum oxychloride content and minimal binder, along with small crystal sizes and increased surface area, the challenges of low bulk density and uneven properties in conventional molybdenum oxychloride compositions are addressed, resulting in efficient and uniform compactions.
Patent Information
- Application Number
- JP2022523589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-21
- Filing Date
- 2020-10-20
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2040-10-20
AI Technical Summary
Conventional molybdenum oxychloride compositions exhibit low bulk density, poor size/shape uniformity, and uneven heat transfer, leading to inefficiencies in pellet formation, deposition, and packaging.
Molybdenum oxychloride consolidated masses with greater than 95% molybdenum oxychloride and less than 10% binder, featuring crystals with average cross-body dimensions less than 5 mm and a surface area greater than 0.0005 cm^2/g, resulting in high bulk density and improved uniformity.
The solution achieves high bulk density compactions with improved size/shape uniformity and heat transfer, reducing the need for frequent reloading in semiconductor processing vessels and enhancing overall production efficiency.
Smart Images

Figure 0007661321000001 
Figure 0007661321000002 
Figure 0007661321000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 923,892, filed October 21, 2019, the entirety of which is incorporated herein by reference.
[0002]
[0002] This disclosure relates to molybdenum oxychloride compositions and compacts, such as pellets, made therefrom. In particular, this disclosure relates to molybdenum oxychloride compositions that exhibit improvements in bulk density, including small amounts, if any, of binder. [Background technology]
[0003]
[0003] Conventional molybdenum oxychloride compositions are often used in powder form, typically in high temperature thin film sublimation processing baths. Generally, these molybdenum oxychloride compositions are synthesized in the form of low density (fluffy) powders, and typically have relatively large average crystallite sizes, e.g., cross body measurements, and / or low surface areas. In operation, the powder is heated to a temperature at which deposition occurs, until sublimation occurs.
[0004] Generally speaking, powders (often with a pelletizing binder) can be pressed into pellets, e.g., tablets. However, powders with relatively large average crystal size often cause problems in pellet formation, possibly due to reduced crystal-to-crystal adhesion potential, potentially resulting in pellets with low bulk density. Importantly, low density pellets are inherently less loaded with powder composition. In the case of molybdenum oxychloride pellets, they may not be rich in molybdenum oxychloride. Thus, low density pellets must often be reloaded into the thin film sublimation processing tank, possibly including some subsequent processing, resulting in downtime and reduced efficiency of the overall process.
[0005]
[0005] In some cases, binders can be added to improve crystal adhesion, thereby facilitating improved pellet formation. Unfortunately, the introduction of binders causes additional problems, such as a reduction in overall pellet purity, and further processing, such as post-pelletization purification or binder "burnout," must be addressed prior to use of the pellets in the proposed application. Importantly, the addition of binders can also contribute to a reduction in the bulk density of the pellets.
[0006] Additionally, conventional molybdenum oxychloride powders suffer from poor particle size uniformity, and / or poor shape uniformity and / or uneven heat transfer throughout their bulk, resulting in inconsistent deposition.
[0007]
[0007] Additionally, conventional molybdenum oxychloride powders present packaging and shipping challenges due to their low density, e.g., the powders (or low density compactions produced therefrom) take up too much volume relative to the practical amount of molybdenum oxychloride. Thus, the ability to effectively use available packaging and shipping is ineffective, and additional packaging and shipping means must be employed. Summary of the Invention [Problem to be solved by the invention]
[0008]
[0008] In view of conventional molybdenum oxychloride technology, there exists a need for improved molybdenum oxychloride compacts, and for molybdenum oxychloride compositions (powders) used in forming the compacts, which exhibit improved physical properties, e.g., increased bulk density and improved size / shape uniformity and heat transfer, while reducing or eliminating the need for binders. [Means for solving the problem]
[0009]
[0009] In some embodiments, the present disclosure relates to molybdenum oxychloride consolidated masses comprising (greater than 95% by weight) molybdenum oxychloride and (less than 10% by weight, e.g., less than 5% by weight) a binder (ceramic binder, cellulose or hydroxyalkyl cellulose, or mixtures thereof). The consolidated masses have a bulk density of greater than 0.85 g / cc, e.g., greater than 1.4 g / cc. The molybdenum oxychloride may comprise crystals, at least 90% of the crystals having an average cross body dimension of less than 5 mm and / or a mass of less than 0.0005 cm. 2 / g. The compacts may have a relative density of greater than 75% and / or a heat transfer uniformity of less than ±10% across the individual compacts. The compacts may have an average diameter dimension of greater than 1 mm.
[0010]
[0010] In some embodiments, the present disclosure relates to a molybdenum oxychloride composition comprising (greater than 95% by weight) molybdenum oxychloride and less than 10% binder. The molybdenum oxychloride composition has a bulk density of greater than 0.75 g / cc and / or a tapped density of greater than 1 g / cc as measured by ASTM B527-2006. The molybdenum oxychloride may comprise crystals, at least 90% of the crystals having an average diameter dimension of less than 1 mm and / or a diameter dimension of less than 0.0005 cm 2 / g.
[0011]
[0011] In some embodiments, the present disclosure relates to a method of making a molybdenum oxychloride compact, the method including the steps of providing a molybdenum oxychloride composition having a bulk density greater than 0.75 g / cc and comprising molybdenum oxychloride and less than 10% binder, and pressing the molybdenum oxychloride composition to form a compact, the compact having a bulk density greater than 1.4 g / cc. In some cases, the pressing includes filling the molybdenum oxychloride composition into a mold and pressing the molded molybdenum oxychloride composition to form a compact. Pressing may be performed at a pressure less than 1000 MPa. The providing step may include synthesizing an intermediate molybdenum oxychloride composition comprising molybdenum oxychloride and less than 10% binder, wherein the intermediate molybdenum oxychloride composition comprises crystals and has a bulk density of less than 0.75 g / cc, and isolating the intermediate molybdenum oxychloride composition to form the molybdenum oxychloride composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] As indicated above, conventional molybdenum oxychloride powders may have a large average crystal size, e.g., diameter measurement, and / or a small surface area (compared to the powders of the present disclosure) and / or may contain a significant amount of binder. As a result, compacts, e.g., pellets, made from the powders have a lower than desired bulk density. Pellets with low bulk density require frequent charging / recharging of the hot semiconductor processing vessels in which they are used (in some cases, the pellets are treated before being used in the vessel), resulting in downtime and reduced efficiency of the overall process. Furthermore, these powders / pellets may suffer from poor particle size and / or shape uniformity, and / or uneven heat transfer throughout the bulk, resulting in inconsistent deposition. Conventional powders / pellets also have problems with packaging and shipping, e.g., pellets take up too much volume for the actual amount of molybdenum oxychloride. Thus, the ability to effectively use available packaging and shipping is ineffective and additional packaging and shipping means must be used.
[0013]
[0013] However, the present inventors have found that certain molybdenum oxychloride powders having relatively small crystals can be effectively pressed into denser compacts, such as pellets. Compacts is a broad term that encompasses the resulting objects formed or molded from compositions, such as the powders disclosed herein. In some cases, the compacts are in the form of pellets, tablets, spheres, disks or pastilles, or combinations thereof. The use of the terms "pellets" or "pelletization" herein is not intended to limit the scope of compacts or the processes / processing involved. For example, a "pellet" may be spherical, and / or "pelletization" may form a spherically shaped compact.
[0014]
[0014] Traditionally, when pelletizing powders with larger crystals, problems such as poor crystal-to-crystal adhesion and low bulk density have been encountered. Without being bound by theory, it is hypothesized that larger crystal structures have a smaller surface area (per unit volume) and therefore a lower opportunity for crystal-to-crystal adhesion, i.e., self-adhesion, to form compacts. In the case of molybdenum oxychloride, by using powders with relatively small crystals, the surface area is improved, allowing for better crystal-to-crystal adhesion and more effective pelletization. Furthermore, it has been surprisingly found that the compacts have a higher bulk density in addition to a higher purity. Advantageously, due to the increased bulk density, the need to reload pellets in the semiconductor processing vessel is significantly reduced. Thus, the overall production efficiency is greatly improved.
[0015]
[0015] In some cases, the powder (and resulting compact) requires less, if any, binder, but also advantageously contributes to reducing or eliminating purity and density related problems associated with binders. Without being bound by theory, it is hypothesized that by using less, if any, low density components, e.g., binders, the overall bulk density of the compact is improved. Also, the need for further processing, e.g., post-pelletization separation or "burning out" of binders prior to using the compact in a semiconductor processing vessel, is beneficially reduced or eliminated.
[0016] It has also been discovered that the dense compacts disclosed herein have more consistent uniformity and heat transfer throughout the compact, advantageously providing more uniform deposition in semiconductor applications.
[0017] Molybdenum oxychloride is a known compound commonly available as a yellow or orange solid. For example, molybdenum oxychloride may have the CAS number 13637-68-8. Molybdenum oxychloride has a density of 3.31 g / cm3 However, conventional molybdenum oxychloride compositions, such as powders, do not reach this density due to the structure of the powder. As noted, conventional molybdenum oxychloride compositions, such as powders or pellets, have a much lower actual, bulk and / or relative density.
[0018] Compacted material
[0018] In some embodiments, the present disclosure relates to molybdenum oxychloride compacts. The compacts include a specific molybdenum oxychloride (powder) and a small amount, if any, of a binder. The compacts have a high bulk density, for example, a bulk density of greater than 1.4 g / cc. Bulk density is a well-known measurement. For example, bulk density can be measured by weighing the amount of material contained in a known volume and calculating the weight per volume of the compact, i.e., the bulk density. Another method of measuring bulk density is provided in ASTM B329- 2006. Molybdenum oxychloride includes crystals of molybdenum oxychloride, and in some embodiments, the crystals are relatively small. As indicated above, the small crystal size surprisingly increases the surface area and allows for better crystal-to-crystal adhesion in the compact, contributing at least in part to the improved bulk density. The molybdenum oxychloride powder itself is discussed in more detail below.
[0019]
[0019] In some embodiments, the bulk density of the compact may be greater than 0.85 g / cc, for example, greater than 0.9 g / cc, greater than 1.0 g / cc, greater than 1.2 g / cc, greater than 1.4 g / cc, greater than 1.5 g / cc, greater than 1.7 g / cc, greater than 2.0 g / cc, greater than 2.1 g / cc, greater than 2.2 g / cc, greater than 2.5 g / cc, greater than 2.7 g / cc or greater than 3.0 g / cc. In terms of range, the bulk density of the compact may be in the range of 0.85 g / cc to 3.1 g / cc, e.g., 0.9 g / cc to 3.1 g / cc, 1.0 g / cc to 3.1 g / cc, 1.2 g / cc to 3.1 g / cc, 1.4 g / cc to 3.1 g / cc, 1.4 g / cc to 3.0 g / cc, 1.4 g / cc to 2.2 g / cc, 1.4 g / cc to 2.8 g / cc, 1.5 g / cc to 2.8 g / cc, 1.6 g / cc to 2.5 g / cc, 1.4 g / cc to 2.0 g / cc, or 1.6 g / cc to 2.0 g / cc.
[0020]
[0020] The compacts can also be characterized in terms of relative density. For example, the relative density of the compacts may be greater than 75%, e.g., greater than 80%, greater than 85%, greater than 86.5%, greater than 87%, greater than 88%, greater than 90%, greater than 92%, greater than 95%, greater than 97%, or greater than 99%. In terms of range, the relative density of the compacts may range from 75% to 99.9%, e.g., 85% to 99%, 88% to 99%, 90% to 98%, 91% to 97%, or 92% to 96%. In some cases, the relative density is a measure of how much air or impurities are present in the pellets. The relative density can be calculated as the ratio of the actual measured density to the maximum theoretical density, e.g., 3.31 for molybdenum oxychloride. The inventors have found that the use of the powders of the present disclosure provides low amounts of air / impurities and unexpectedly provides improvements in density and conductivity.
[0021] In some embodiments, by using molybdenum oxychloride powder having relatively small crystallites, denser compacts can be achieved, in many cases, without the use of binders.
[0022] In some embodiments, at least 90% of the molybdenum oxychloride crystals have an average diameter dimension of less than 5 mm, e.g., less than 4 mm, less than 3 mm, less than 2 mm, less than 1 mm, less than 0.7 mm, less than 0.5 mm, less than 0.3 mm, less than 0.1 mm, or less than 0.05 mm. In terms of range, at least 90% of the crystals may have an average diameter dimension in the range of 0.01 mm to 5 mm, e.g., 0.05 mm to 3 mm, 0.05 mm to 2 mm, 0.1 mm to 3 mm, 0.1 mm to 2 mm, 0.1 mm to 1 mm, 0.3 mm to 3 mm, 0.3 mm to 2 mm, or 0.5 mm to 1.5 mm. In terms of the lower limit, at least 90% of the molybdenum oxychloride crystals have an average diameter dimension greater than 0.01 mm, such as greater than 0.05 mm, greater than 0.1 mm, greater than 0.3 mm, greater than 0.5 mm, or greater than 0.7 mm.
[0023] In some embodiments, the crystals of the compact can have a large surface area. For example, the crystals can have an area of less than 0.0005 cm 2 / g, e.g., 0.001 cm 2 / g, 0.005 cm 2 / g, 0.007 cm 2 / g, 0.01 cm 2 / g, 0.012 cm 2 / g, 0.015 cm 2 / g, 0.017 cm 2 / g, 0.02 cm 2 / g, 0.025 cm 2 / g, 0.05 cm 2 / g, 0.1 cm 2 / g or 0.25 cm 2 In terms of range, the crystals may have a surface area of greater than 0.0005 cm / g. 2 / g~1.0cm 2 / g, e.g., 0.001 cm 2 / g~0.5cm 2 / g, 0.005cm 2 / g~0.1cm 2 / g, 0.007cm 2 / g~0.1cm 2 / g, 0.01cm 2 / g~0.1cm 2 / g or 0.012cm 2 / g~0.05cm 2 / g.
[0024]
[0024] In some cases, the molybdenum oxychloride compact is a high purity pellet. For example, the compact may contain more than 95% by weight, for example, more than 96% by weight, more than 97% by weight, more than 98% by weight, more than 99% by weight, or more than 99.5% by weight of molybdenum oxychloride. In terms of range, the compact may contain 80% to 99.999% by weight, for example, 90% to 99.999% by weight, 95% to 99.99% by weight, or 97% to 99% by weight of molybdenum oxychloride. In terms of lower limit, the compact may contain less than 99.99% by weight, for example, less than 99.9% by weight, less than 99.5% by weight, less than 99.3% by weight, or less than 99% by weight of molybdenum oxychloride. Surprisingly, the use of less binder, if any, in the compact, e.g., impurities, advantageously contributes to improved purity.
[0025]
[0025] As indicated above, the use of little, if any, binder has provided the aforementioned benefits. In some embodiments, the compact comprises less than 10 wt. % binder, e.g., less than 5 wt. %, less than 3 wt. %, less than 1 wt. %, less than 0.7 wt. %, 0.5 wt. %, or less than 0.1 wt. %. In terms of ranges, the compact comprises between 0.1 wt. % and 10 wt. % binder, e.g., between 0.1 wt. % and 8 wt. %, between 0.5 wt. % and 7 wt. %, between 1 wt. % and 6 wt. %, or between 2 wt. % and 5 wt. %.
[0026] Pelletizing binders are well known in the art. Exemplary binders include ceramic binders, cellulose and hydroxyalkyl cellulose. An exemplary commercial product is Klucel™ hydroxypropyl cellulose from Ashland Chemical.
[0027]
[0027] It has been discovered that the use of the powders of the present disclosure (in some cases containing little, if any, binder) unexpectedly provides improved heat transfer uniformity throughout the individual compactions. Without being bound by theory, it is believed that the denser compacts have less air and / or impurities disposed therein. As a result, the overall conductivity and heat transfer properties of the compacts are improved. In some embodiments, the compacts have a heat transfer uniformity of less than ±10%, e.g., less than ±8%, less than ±5%, less than ±3%, less than ±1%, less than ±0.5%, or less than ±0.1%, throughout the individual compactions.
[0028]
[0028] The size of the compacts may vary widely. In some cases, the compacts may have an average diameter dimension, e.g., a length of greater than 1 mm, e.g., greater than 3 mm, greater than 5 mm, greater than 7 mm, greater than 10 mm, greater than 12 mm, greater than 15 mm, greater than 17 mm, greater than 20 mm, greater than 24 mm, or greater than 30 mm.
[0029] powder As indicated above, the compacts are formed from certain powders. In some embodiments, the molybdenum oxychloride powder (molybdenum oxychloride composition) comprises molybdenum oxychloride and little, if any, binder, e.g., less than 10% binder. The molybdenum oxychloride powder has a bulk density of greater than 0.75 g / cc. The molybdenum oxychloride powder is pressed into the compacts. Thus, many of the aforementioned compositional features, characteristics, and property measurements of the compacts also apply to the powders, e.g., molybdenum oxychloride and binder concentrations, crystal size, surface area, etc. However, in some cases, the powders may have low density characteristics, e.g., the powders may not be as dense as pellets.
[0030]
[0030] In some embodiments, the bulk density of the powder may be greater than 0.55 g / cc, for example, greater than 0.65 g / cc, greater than 0.75 g / cc, greater than 0.8 g / cc, greater than 0.85 g / cc, greater than 0.9 g / cc, greater than 1.0 g / cc, greater than 1.2 g / cc, greater than 1.5 g / cc, greater than 2.0 g / cc, or greater than 2.5 g / cc. In terms of range, the bulk density of the powder may be in the range of 0.55 g / cc to 3.31 g / cc, for example, 0.65 g / cc to 3.31 g / cc, 0.70 g / cc to 3.31 g / cc, 0.75 g / cc to 3.31 g / cc, 0.77 g / cc to 3.0 g / cc, 0.78 g / cc to 2.5 g / cc, 0.77 g / cc to 2.0 g / cc, 0.55 g / cc to 2.0 g / cc, 0.7 g / cc to 1.8 g / cc, 1.0 g / cc to 1.5 g / cc, 1.2 g / cc to 1.3 g / cc.
[0031]
[0031] The powder may have a high tap density in some cases. For example, the tap density of the powder may be greater than 0.5g / cc, such as greater than 0.6g / cc, greater than 0.7g / cc, greater than 0.8g / cc, greater than 0.85g / cc, greater than 0.9g / cc, greater than 1.0g / cc, greater than 1.2g / cc, greater than 1.5g / cc, or greater than 2.0g / cc. In terms of range, the tap density of the powder may be in the range of 0.5g / cc to 3.5g / cc, such as 0.5g / cc to 2.0g / cc, 0.6g / cc to 1.8g / cc, 0.7g / cc to 1.5g / cc, 0.8g / cc to 1.3g / cc, 0.9g / cc to 1.1g / cc, or 0.95g / cc to 1.05g / cc. Tap density may be measured by ASTM B527-2006.
[0032] In some cases, the bulk density of the compact may be at least 5% greater, at least 10% greater, at least 25% greater, at least 50% greater, at least 75% greater, or at least 100% greater than the bulk density of the powder.
[0033] Method for Producing a Compacted Product
[0033] The present disclosure also relates to a method of making a compact, the method including the steps of providing a molybdenum oxychloride powder and pressing the powder to form a compact, the compact having the properties discussed herein.
[0034]
[0034] In some cases, the pressing step may include packing the powder into a mold and compressing the molded powder to form a compact. The inventors have found that the particular powders disclosed herein provide processing benefits. For example, the more completely the powder fills the mold, the less, if any, the powder leaves behind as air pockets and / or other impurities that can affect, for example, pellet composition, density and / or conductivity. Without being bound by theory, it is hypothesized that the smaller size crystals aid in this improved packing of the mold. As a result, a high density, high performance compact is formed.
[0035] In some cases, pressing of the molding powders can be carried out at lower pressures than those used when conventional powders are used. It is believed that the smaller crystals and larger surface area of the powders favorably contribute to crystal-to-crystal adhesion, allowing compacts to form under lower pressures.
[0036]
[0036] In some embodiments, the pressurization is performed at a pressure of less than 1000 MPa, for example, less than 800 MPa, less than 750 MPa, less than 700 MPa, less than 650 MPa, less than 600 MPa. In terms of range, the pressurization may be performed at a pressure in the range of 50 MPa to 1000 MPa, for example, 100 MPa to 1000 MPa, 50 MPa to 500 MPa, 50 MPa to 400 MPa, 50 MPa to 300 MPa, 75 MPa to 400 MPa, 100 MPa to 300 MPa, 100 MPa to 200 MPa, 200 MPa to 900 MPa, 300 MPa to 800 MPa, 400 MPa to 700 MPa, or 400 MPa to 650 MPa. Advantageously, the low pressure improves the working efficiency and also contributes to improved wear of the device.
[0037]
[0037] In another embodiment, preparing the powder includes the step of synthesizing an intermediate molybdenum oxychloride composition (powder) comprising molybdenum oxychloride and less than 10% binder. The intermediate molybdenum oxychloride composition comprises crystals and has a bulk density of less than 0.75 g / cc. The method further includes the step of separating the intermediate molybdenum oxychloride composition to form a molybdenum oxychloride composition. In this step, the bulk density of the intermediate molybdenum oxychloride powder is increased to obtain the aforementioned molybdenum oxychloride powder. In some cases, larger crystals may be removed from the intermediate molybdenum oxychloride powder, for example, via sieving or other size-related separation methods. EXAMPLES
[0038] The following examples are provided to illustrate the compositions and methods of the present disclosure. The examples are merely illustrative and are not intended to limit the disclosure to the materials, conditions, or process parameters set forth herein.
[0039]
[0039] Molybdenum oxychloride powders of Examples 1 and 2 having smaller crystal size, e.g., less than 5 mm, e.g., approximately 0.8 mm to 2 mm, were prepared as described herein. The powders were loaded into a graduated glass container of approximately 870 cc volume. Advantageously, due to the minimal binder content (if any), no burn-out of the powder was performed. Conventional powder of Comparative Example A having a larger crystal size was loaded into a similar graduated glass container. The loaded container was weighed, whereby the bulk density was calculated. The results are shown in Table 1.
[0040] [Table 1]
[0041] As shown, the powders of Examples 1 and 2 exhibit significantly higher bulk densities, e.g., greater than 1.4 g / cc. This high density advantageously allows for denser compactions, e.g., denser powders. Advantageously, the denser powders contain more molybdenum oxychloride, which in use can significantly reduce the need to recharge molybdenum oxychloride pellets in semiconductor processing vessels.
[0042]
[0041] Molybdenum oxychloride powders of Examples 3 and 4 having smaller crystallite sizes than those described herein were prepared and formed into tablets as shown in Table 2. Advantageously, due to the minimal binder content (if any), powder burnout was not performed. Conventional powders of Comparative Examples B and C having larger crystallite sizes were similarly prepared and formed into tablets as shown in Table 2. Relative densities were calculated by comparing the tablet densities with the maximum theoretical density of 3.31.
[0043] [Table 2]
[0044] As shown in Table 2, the tablets of Examples 3 and 4 exhibit much higher tablet density and relative density than the conventional tablets of Comparative Examples B and C. Advantageously, the tablets of Examples 3 and 4 contain more molybdenum oxychloride, which in use can significantly reduce the need to recharge molybdenum oxychloride pellets in semiconductor processing vessels.
[0045]
[0043] Molybdenum oxychloride powders of Examples 5-12 were prepared having smaller crystallite sizes than those described herein. The powders were measured for tap density, as measured by ASTM B527-2006. A conventional powder of Comparative Example D, having a larger crystallite size, was similarly measured for tap density. The results are shown in Table 3.
[0046] [Table 3]
[0047] As shown in Table 3, the tablets of Examples 5-12 exhibit tap densities well above 0.5 g / cc, e.g., above 0.80 g / cc. In fact, in most cases, the tap densities were greater than 1.0 g / cc. As shown, Comparative Example D exhibited a tap density of 0.80 g / cc, which is 12% less than even the smallest working example (Example 10) ((0.91-0.8) → 0.11 / 0.91 = 12%). The tap density of Comparative Example A was also less than that of Examples 5-12. Advantageously, in use, the disclosed higher tap density powders provide superior packing and do not require as much compression as would be necessary for powders having lower tap densities.
[0048] Embodiment
[0045] Among other things, the following embodiments are disclosed:
[0049] and less than 10 wt.% of a binder. The compact has a bulk density of greater than 0.85 g / cc, such as greater than 1.4 g / cc.
[0050]
[0047] Embodiment 2: An embodiment of embodiment 1, wherein the molybdenum oxychloride comprises crystals, at least 90% of the crystals having an average diameter dimension of less than 5 mm.
[0048] Embodiment 3: The embodiment of embodiment 1 or 2, wherein the compact comprises greater than 95% by weight molybdenum oxychloride.
[0051]
[0049] Embodiment 4: An embodiment described in any one of embodiments 1-3, wherein the compact has a relative density of greater than 75%.
[0050] Embodiment 5: An embodiment described in any one of embodiments 1-4, wherein the compacts have a heat transfer uniformity of less than ±10% across each individual compact.
[0052]
[0051] Embodiment 6: The molybdenum oxychloride comprises crystals, the crystals being 0.0005 cm 2 The embodiment of any one of embodiments 1-5, having a surface area of greater than 1 / g.
[0052] Embodiment 7: An embodiment described in any one of embodiments 1-6, wherein the compact has an average diameter dimension of greater than 1 mm.
[0053]
[0053] Embodiment 8: An embodiment described in any one of embodiments 1-7, comprising less than 5 wt. % of a ceramic binder, comprising cellulose or hydroxyalkyl cellulose or a mixture thereof.
[0054] and less than 10% of a binder. The molybdenum oxychloride composition has a bulk density greater than 0.75 g / cc.
[0055]
[0055] Embodiment 10: An embodiment described in embodiment 9, wherein the molybdenum oxychloride comprises crystals, and at least 90% of the crystals have an average diameter dimension of less than 1 mm.
[0056] Embodiment 11: The embodiment of embodiment 9 or 10, wherein the molybdenum oxychloride composition comprises greater than 95% by weight of molybdenum oxychloride.
[0056]
[0057] Embodiment 12: The embodiment of any one of embodiments 9-11, wherein the molybdenum oxychloride composition has a tap density, as measured by ASTM B527-2006, of greater than 0.5 g / cc, such as greater than 1 g / cc.
[0057]
[0058] Embodiment 13: The molybdenum oxychloride comprises crystals, the crystals being 0.0005 cm 2 The embodiment of any one of embodiments 9-12, having a surface area of more than 1 / g.
[0059] Embodiment 14: A method of making a molybdenum oxychloride compact, comprising providing a molybdenum oxychloride composition having a bulk density greater than 0.75 g / cc and comprising molybdenum oxychloride and less than 10% binder, and pressing the molybdenum oxychloride composition to form a compact, wherein the compact has a bulk density greater than 1.4 g / cc.
[0058]
[0060] Embodiment 15: The embodiment of embodiment 14, wherein the pressing step comprises charging the molybdenum oxychloride composition into a mold and pressing the shaped molybdenum oxychloride composition to form a compact.
[0059]
[0061] Embodiment 16: The embodiment of embodiment 14 or 15, wherein the pressurizing step is carried out at a pressure of less than 1000 MPa.
[0062] Embodiment 17: The embodiment of any one of embodiments 14-16, wherein the preparing step includes synthesizing an intermediate molybdenum oxychloride composition comprising: molybdenum oxychloride; and less than 10% of a binder, wherein the intermediate molybdenum oxychloride composition comprises crystals and has a bulk density of less than 0.75 g / cc; and isolating the intermediate molybdenum oxychloride composition to form a molybdenum oxychloride composition.
[0060]
[0063] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be readily apparent to those skilled in the art. In view of the above discussion, the knowledge related to the art in connection with the background art and detailed description and the disclosures of the references discussed above are incorporated herein by reference in their entirety. Furthermore, it should be understood that aspects of the present invention and parts of various embodiments, as well as various features described below and / or in the appended claims, may be combined or exchanged either in whole or in part. In the above description of various embodiments, an embodiment referring to another embodiment may be appropriately combined with other embodiments as recognized by those skilled in the art. Furthermore, those skilled in the art will recognize that the above description is merely exemplary and is not intended to be limiting. Specific embodiments of the present invention are as follows. [1] Molybdenum oxychloride compacts, Molybdenum oxychloride, and less than 10% by weight of a binder. Including, A compact having a bulk density of greater than 0.85 g / cc. [2] 2. The method of claim 1, wherein the molybdenum oxychloride comprises crystals, and at least 90% of the crystals have an average diameter dimension of less than 5 mm. [3] 2. The compact according to claim 1, comprising more than 95% by weight of molybdenum oxychloride. [4] The compact described in [1] has a relative density of more than 75%. [5] The compact of [1], having a heat transfer uniformity of less than ±10% throughout the individual compacts. [6] The molybdenum oxychloride comprises crystals, the crystals being 0.0005 cm 2 The compact according to [1], having a surface area of more than 1 / g. [7] The compact according to [1], having an average diameter dimension of more than 1 mm. [8] 13. The compact of claim 1, comprising less than 5% by weight of a binder comprising a ceramic binder, cellulose, or hydroxyalkyl cellulose, or a mixture thereof. [9] 1. A molybdenum oxychloride composition comprising: Molybdenum oxychloride and With less than 10% binder Including, The composition has a bulk density of greater than 0.75 g / cc.
[10] 10. The composition of claim 9, wherein the molybdenum oxychloride comprises crystals, at least 90% of the crystals having an average diameter dimension of less than 1 mm.
[11] The composition according to [9], comprising more than 95% by weight of molybdenum oxychloride.
[12] [9] The composition of claim 1, having a tap density of greater than 0.5 g / cc as measured by ASTM B527-2006.
[13] The molybdenum oxychloride comprises crystals, the crystals being 0.0005 cm 2 The composition described in [9] has a surface area of more than 1 / g.
[14] 1. A method for producing molybdenum oxychloride compacts, comprising the steps of: Has a bulk density greater than 0.75 g / cc; and Molybdenum oxychloride, and Less than 10% binder providing a molybdenum oxychloride composition comprising: pressing said molybdenum oxychloride composition to form said compact having a bulk density of greater than 1.4 g / cc; The method includes:
[15] The pressing step further comprises: charging the molybdenum oxychloride composition into a mold; pressing the shaped molybdenum oxychloride composition to form said compact; The method according to claim 14, comprising:
[16] The method according to
[15] , wherein the pressurizing step is carried out at a pressure of less than 1000 MPa.
[17] The preparing step further comprises: Molybdenum oxychloride, and Less than 10% binder wherein the intermediate molybdenum oxychloride composition comprises crystals and has a bulk density of less than 0.75 g / cc; separating said intermediate molybdenum oxychloride composition to form said molybdenum oxychloride composition; The method according to claim 14, comprising:
Claims
1. Molybdenum oxychloride compacts, Molybdenum oxychloride, less than 10% by weight of a binder; Including, has a relative density of greater than 86.5% compared to the maximum theoretical density of the molybdenum oxychloride of 3.31 g / cc; At least 90% of the crystals of the molybdenum oxychloride have an average diameter dimension in the range of 0.01 mm to 5 mm. Compacted material.
2. 10. The compact of claim 1 comprising greater than 95% by weight of molybdenum oxychloride.
3. 10. The compact of claim 1 having a heat transfer uniformity of less than ±10% across the individual compacts.
4. The molybdenum oxychloride comprises crystals, the crystals being 0.0005 cm 2 2. The compact of claim 1 having a surface area of greater than 1.0 μm / g.
5. 2. The compact of claim 1 having an average diameter dimension of greater than 1 mm.
6. 10. The compact of claim 1 comprising less than 5% by weight of a binder comprising a ceramic binder, cellulose, or hydroxyalkyl cellulose, or a mixture thereof.
7. 1. A molybdenum oxychloride composition for forming a molybdenum oxychloride compact comprising: Molybdenum oxychloride and Less than 10% binder Including, the molybdenum oxychloride composition has a bulk density of greater than 0.85 g / cc or a tapped density of greater than 0.8 g / cc as measured by ASTM B527-2006; and the molybdenum oxychloride comprises crystals, and at least 90% of the crystals have an average diameter dimension in the range of 0.01 mm to 5 mm; and the molybdenum oxychloride compact has a relative density of greater than 86.5% compared to the maximum theoretical density of the molybdenum oxychloride of 3.31 g / cc; composition.
8. 8. The composition of claim 7 comprising greater than 95% by weight of molybdenum oxychloride.
9. The crystal is 0.0005 cm 2 8. The composition of claim 7 having a surface area of greater than 1.0 μm / g.
10. 1. A method for producing molybdenum oxychloride compacts, comprising the steps of: has a bulk density greater than 0.85 g / cc; and Molybdenum oxychloride crystals, and Less than 10% binder providing a molybdenum oxychloride composition comprising: pressing said molybdenum oxychloride composition to form said compact having a bulk density of greater than 1.4 g / cc; Including, the bulk density of the compact is at least 5% greater than the bulk density of the molybdenum oxychloride composition; At least 90% of the crystals of the molybdenum oxychloride have an average diameter dimension in the range of 0.01 mm to 5 mm; and The molybdenum oxychloride compact has a relative density of greater than 86.5% compared to the maximum theoretical density of the molybdenum oxychloride of 3.31 g / cc. method.
11. The pressing step further comprises: charging the molybdenum oxychloride composition into a mold; pressing the shaped molybdenum oxychloride composition to form said compact; The method of claim 10, comprising:
12. The method of claim 11 , wherein the pressurizing step is carried out at a pressure of less than 1000 MPa.
13. The preparing step further comprises: Molybdenum oxychloride, and Less than 10% binder wherein the intermediate molybdenum oxychloride composition comprises crystals and has a bulk density of less than 0.75 g / cc; separating said intermediate molybdenum oxychloride composition to form said molybdenum oxychloride composition; The method of claim 10, comprising:
Citation Information
Patent Citations
Low temperature sintering of solid precursors
JP2018535315A
Solid material pre-treatment method and solid material product filled with solid material produced by the solid material pre-treatment method
JP2019104659A
Method for producing high-bulk-density molybdenum oxychloride
WO2020021786A1